Hybrid Vegetable/Glass Fiber Composites - Amico, Sandro C.; D'Almeida, José R.M.; De Carvalho, Laura H.; Cioffi, Ma. Odila H. [UNESP] (Wiley, 2014)
There is an ever-growing worldwide interest in the use of lignocellulosic fibers as reinforcement in either thermoset (mainly unsaturated polyester) or thermoplastic (mainly polyolefins) composites. However, the wider use of these fibers for replacing synthetic ones is limited by disadvantages like their comparatively poorer mechanical properties, higher moisture absorption, lower compatibility to polymers, fiber heterogeneity, inferior durability and also flammability. Among the ways of minimizing these drawbacks, the concomitant use of vegetable and synthetic fibers, i.e., producing hybrid composites, is among the most promising strategies. For instance, hybridization with glass fiber, the most used synthetic fiber, is an unquestionable way of incrementing overall mechanical and thermal properties. In this context, this chapter presents a review of the state-of-the-art of hybrid vegetable/glass fiber composites, focusing on the hybridization effect on the properties of thermoplastic and thermoset polymer matrices composites.
Keywords: Glass fiber; Hybrid composites; Thermoplastic; Thermoset; Vegetable fibers